Severe Presentation of Nontypeable Haemophilus influenzae (NTHi) Infection in a Previously Healthy Toddler - Eiman Al Boloushi; Abdulla Al Amri; Ghassan Ghatasheh; Huda Al Dhanhani (Case Reports in Infectious Diseases)
Background. Cellulitis is the inflammation of the skin and subcutaneous tissue. It is usually caused by Gram-positive organisms such as Staphylococcus and Streptococcus pyogenes infection. Nontypeable Haemophilus influenzae (NTHi) is an uncommon cause of cellulitis. Hence, we report on this case. Case Presentation. A previously healthy 19-month-old girl presented with a fever and two-day history of progressive right leg swelling and redness. Her physical examination revealed significant induration and swelling of her right lower leg but no obvious signs of abscess formation. Given the clinical picture, she was admitted as a case of cellulitis. Parenteral clindamycin was started empirically, as the blood culture preliminary report showed Gram-negative rods. Ceftriaxone was added to broaden the coverage. Final blood culture grew NTHi. Despite the use of proper antibiotics (amoxicillin clavulanic acid), the clinical course was complicated with abscess formation that required surgical intervention. Conclusions. We are reporting a previously healthy child who developed NTHi cellulitis of the lower leg. To the best of our knowledge, there have been no formal reports pertaining to leg cellulitis following infection by NTHi, yet published in UAE, and reports of HIB cellulitis of the extremities still appear to be rare; hence, we report on this case.